Aspartic acid at position 57 of the HLA-DQ beta chain protects against type I diabetes: a family study. - Morel, P A (1988)
One hundred seventy-two members from 27 randomly selected multiple case Caucasian families of patients with insulin-dependent diabetes mellitus (IDDM) were studied at the DNA level to ascertain the reliability of codon 57 of the HLA-DQ beta-chain gene as a disease protection/susceptibility marker. The analysis was carried out by polymerase chain reaction amplification of DNA encoding the first domain of the DQ beta chain and by dot blot analysis of the amplified material with allele-specific oligonucleotide probes. One hundred twenty-three randomly selected healthy Caucasian donors were also tested. The results demonstrated that haplotypes carrying an aspartic acid in position 57 (Asp-57) of their DQ beta chain were significantly increased in frequency among nondiabetic haplotypes (23/38), while non-Asp-57 haplotypes were significantly increased in frequency among diabetic haplotypes (65/69). Ninety-six percent of the diabetic probands in our study were homozygous non-Asp/non-Asp as compared to 19.5% of healthy unrelated controls. This conferred a relative risk of 107 (chi 2 = 54.97; P = 0.00003) for non-Asp-57 homozygous individuals. Even though the inheritance and genetic features of IDDM are complex and are not necessarily fully explained by DQ beta chain polymorphism, this approach is much more sensitive than HLA serolog in assessing risk for IDDM.